The Influence of Learning Motivation, Vocabulary Mastery, Self-Confidence, and Classroom Interaction on Students' English-Speaking Ability - Suhardianto Suhardianto; Evi Martiningsih; Petrus Jacob Pattiasina; Shaumiwaty Shaumiwaty (PT. BATARI EDU CALYA, 2026)
This study examined the influence of learning motivation, vocabulary mastery, self-confidence, and classroom interaction on students' English-speaking ability. A quantitative correlational design was employed. The population comprised junior and senior high school students in Indonesia during the 2025/2026 academic year, from which 96 students were selected through simple random sampling. Data were collected using questionnaires measuring learning motivation, self-confidence, and classroom interaction, a vocabulary mastery test, and a speaking performance assessment. Before analysis, all instruments underwent validity and reliability testing. The data were analyzed using descriptive statistics and multiple linear regression in IBM SPSS Statistics after the assumptions of normality, linearity, multicollinearity, and homoscedasticity had been assessed. The results showed that learning motivation, vocabulary mastery, self-confidence, and classroom interaction each had a positive and statistically significant influence on students' English-speaking ability. Collectively, the four independent variables significantly explained students' speaking performance, with the regression model accounting for 73.5% of the variance in English-speaking ability. Vocabulary mastery was the strongest predictor, followed by classroom interaction, learning motivation, and self-confidence. These findings indicate that improving students' speaking competence requires an integrated instructional approach that promotes vocabulary development, strengthens learning motivation and self-confidence, and facilitates meaningful classroom interaction. The study offers practical implications for English teachers seeking to design more effective communicative language-learning environments.